A century of teaching machines, 50 years of machines to learn with - Fino, Carlos Nogueira (Revista Hipótese, 2017)
This article reflects critically on teaching machines, their genesis and their behaviorist foundations, from a Thorndike’s conjecture made in 1912 to the beginning of their migration to virtual media in 1960. Next, it presents the tradition of machines to learn with by going back to the creation of the Logo language, in 1967, inspired by the constructivism and the constructionism. It concludes by denying that the antinomy between teaching machines and machines to learning with has been overcome.